PENGARUH DANA PERIMBANGAN DAN PENDAPATAN ASLI DAERAH (PAD) TERHADAP PERTUMBUHAN EKONOMI MELALUI BELANJA MODAL DI KOTA DALAM WILAYAH JAWA TIMUR (TAHUN 2009-2014) - Fani Wiraswasta; M. Pudjihardjo; Putu Mahardika Adis (University of Merdeka Malang, 2018)
This research aims to examine and anylize the effects of balance fund and local revenue to the economics growth trhough capital expenditure in the city of east java from 2009 to 2014. The samples was determined by purposive sampling or judgement sampling technique in which taking from financial statement data of eight cities in east java particularly in local revenue, capital expenditure, and economics growth report in the period 2009-2014. The secondary data was collected from budget revenue and expenditure of local government (APBD) obtained from the website of Directorate general of local givernmant for fiscal balance that consist of budget revenue and expenditure, local revenue (PAD), general allocation fund (DAU), and special allocation fund (DAK). While, for economics growth, this research uses data from BPS report. In addition, multiple regression was used to anylize data by SPSS 17 and path analysis also used to test the hypotheses. This study found that all hipotheses were accepted. The balance fund and local government revenue have positive and significant effects to capital expenditure directly and to economics growth directly and indirectly. DOI : https://doi.org/10.26905/jbm.v5i2.2390